Developing a Salutogenic Food-Based Taiyaki to Strengthen Family and Community Capacity for Healthy Eating - Salsabila Romadona; Rita Ismawati (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Strengthening family and community capacity for healthy eating remains a key challenge in health promotion, particularly in Indonesia, where child stunting persists. Objective: This study aimed to develop a salutogenic food-based taiyaki using moringa leaves and mung bean flour and to interpret its potential role in strengthening family and community capacity for healthy eating. Methods: A two-phase descriptive analytic design was applied. Phase 1 involved experimental food product development through five formulation trials using partial substitution with moringa leaves and mung bean flour, followed by expert sensory evaluation and nutritional content analysis using NutriSurvey software. Phase 2 consisted of a literature-based salutogenic health promotion analysis guided by salutogenesis theory, health promotion principles, and a social marketing framework to interpret potential contributions to capacity building. Results: The optimized taiyaki formulation with moringa leaves and mung bean flour demonstrated good sensory acceptability by expert panelists, alongside improved nutritional content, particularly in protein, iron, zinc, dietary fiber, and selected vitamins. These findings indicate that familiar snack foods can be nutritionally enhanced using locally available ingredients without compromising their acceptability. A Salutogenic perspective showed that the product’s familiar format and clear nutritional value enhance comprehensibility, the use of accessible ingredients supports manageability, and the culturally acceptable, child-friendly presentation strengthens meaningfulness. Conclusion: Food-based taiyaki modified with moringa leaves and mung bean flour shows potential as a salutogenic health promotion strategy to strengthen family and community capacity for healthy eating and provides a foundation for future community-based implementation.